Dental glass ionomer cement liquid and dental glass ionomer cement
The dental glass ionomer cement liquid, containing a polycarboxylic acid-based polymer, water, a water reducing agent, and a pH buffering component, addresses the issue of rapid hardening by extending the operation time and enhancing the physical strength and adhesion of the cement-hardened body.
Patent Information
- Application Number
- JP2020569372
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-30
- Filing Date
- 2019-10-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2039-10-24
AI Technical Summary
Dental glass ionomer cement hardens too quickly when a high proportion of powder components is used, making it difficult to achieve a cement-hardened body with high physical strength while ensuring appropriate operation time for clinical use.
A dental glass ionomer cement liquid comprising a polycarboxylic acid-based polymer, water, a water reducing agent, and a pH buffering component, which slows down the hardening process and allows for a longer operation time while maintaining high physical strength.
The solution enables the attainment of a cement-hardened body with high physical strength and improved adhesion to teeth, while ensuring a suitable operation time for clinical applications.
Smart Images

Figure 0007665883000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental glass ionomer cement liquid to be used by mixing with a dental glass ionomer cement powder component mainly composed of aluminosilicate glass, and a dental glass ionomer cement. [Background technology]
[0002] Dental glass ionomer cement is used by reacting a polymer acid, whose main component is an acid such as polycarboxylic acid, with glass powder for glass ionomer cement in the presence of water and hardening it. Glass ionomer cement has excellent affinity with living bodies, and the hardened body is translucent and has excellent aesthetics. In addition, glass ionomer cement has excellent adhesive strength to tooth tissues such as enamel and dentin, and furthermore, when fluorine is contained in the glass powder, it has excellent properties such as anti-caries effect due to the fluorine. Therefore, glass ionomer cement is a material that is widely used in the dental field for filling carious cavities, bonding crowns, inlays, bridges and orthodontic bands, lining cavities, root canal filling sealer, abutment construction and preventive plugging.
[0003] Dental glass ionomer cement is generally composed of a powder component containing fluoroaluminosilicate glass and a liquid component containing a polycarboxylic acid polymer (see, for example, Patent Document 1). This cement is used by mixing and kneading the powder component and the liquid component to form a kneaded mixture, which is applied to the treatment site and then hardened. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-91689 A Summary of the Invention [Problem to be solved by the invention]
[0005] Here, in order to obtain a hardened dental glass ionomer cement with high physical strength, it is considered to increase the ratio of the powder component when mixing and kneading the powder component containing the aluminosilicate glass and the liquid component containing the polycarboxylic acid polymer. However, when the ratio of the powder component is increased, the cement hardens too quickly, resulting in a problem that there is no time margin for clinical use. In other words, it is difficult to obtain a hardened cement with high physical strength while ensuring an appropriate operating margin for clinical use.
[0006] Therefore, an object of the present invention is to provide a dental glass ionomer cement liquid which can provide a hardened cement product with high physical strength while ensuring an appropriate operating time for clinical use. [Means for solving the problem]
[0007] One aspect of the present invention is a composition comprising a polycarboxylic acid polymer, water, a water reducing agent, and a pH buffer component, the polycarboxylic acid polymer being a polymer of an α-β unsaturated monocarboxylic acid or an α-β unsaturated dicarboxylic acid, and the water reducing agent being It is a water-soluble salt of a copolymer of methacrylic acid and acrylic acid having a polyoxyethylene chain. The pH buffering component is a dental glass ionomer cement liquid that includes one or more of tartaric acid, citric acid, malic acid, ethylenediaminetetraacetic acid, lactic acid, butyric acid, barbituric acid, phosphoric acid, acetic acid, and oxalic acid, and water-soluble salts thereof. Effect of the Invention
[0008] According to one aspect of the present invention, a dental glass ionomer cement liquid can be used to obtain a hardened cement product having high physical strength while ensuring an appropriate operating time for clinical use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Next, an embodiment of the present invention will be described. <Dental glass ionomer cement liquid> The dental glass ionomer cement liquid of the present embodiment contains a polycarboxylic acid polymer, water, and a water reducing agent.
[0010] The polycarboxylic acid polymer is a component necessary for the reaction with the aluminosilicate glass powder contained in the powder component described later. By mixing and kneading the dental glass ionomer cement liquid and the powder component, an acid-base reaction occurs in which aluminum ions eluted from the aluminosilicate glass powder and the conjugate base of the polycarboxylic acid polymer ionically crosslink, and the mixture hardens.
[0011] The polycarboxylic acid polymer is a polymer of α-β unsaturated monocarboxylic acid or α-β unsaturated dicarboxylic acid. For example, a copolymer or homopolymer containing one or more selected from acrylic acid, methacrylic acid, 2-chloroacrylic acid, 3-chloroacrylic acid, aconitic acid, mesaconic acid, maleic acid, itaconic acid, fumaric acid, glutaconic acid, and citraconic acid is an example of the polycarboxylic acid polymer. Two or more of these may be used.
[0012] The polycarboxylic acid polymer preferably does not contain a polymerizable ethylenically unsaturated double bond.
[0013] The polycarboxylic acid polymer preferably has a mass average molecular weight of 5,000 to 40,000. When the mass average molecular weight is 5,000 or more, the physical strength of the hardened body is high and the adhesive strength to the tooth structure is also improved. When the mass average molecular weight is 40,000 or less, the dental glass ionomer cement liquid has a suitable viscosity and is easy to knead.
[0014] The amount of polycarboxylic acid polymer blended in the dental glass ionomer cement liquid is preferably 5 to 60% by mass. When the amount of polycarboxylic acid polymer blended is 5% by mass or more, the adhesiveness to tooth structure, which is a characteristic of dental glass ionomer cement, is improved. When the amount of polycarboxylic acid polymer blended is 60% by mass or less, the durability of the hardened body is improved. The amount is more preferably 20 to 50% by mass.
[0015] Water is a necessary component for the acid-base reaction between the aluminosilicate glass powder and the polycarboxylic acid polymer.
[0016] The amount of water may be the balance of the other components, but is preferably 30 to 80% by mass in the dental glass ionomer cement liquid. When the amount of water is 30% by mass or more, the kneading property is improved. When the amount of water is 80% by mass or less, the physical strength of the hardened body is high. More preferably, it is 40 to 70% by mass.
[0017] The water reducing agent has the effect of preventing the cement from hardening too quickly during the acid-base reaction caused by mixing and kneading the dental glass ionomer cement liquid and the powder component, even if the ratio of the powder component is increased.
[0018] Examples of the water reducing agent include lignin sulfonate-based, oxycarboxylate-based, naphthalene sulfonate-based, melamine sulfonate-based, polystyrene sulfonate-based, polycarboxylate-based, and the like.
[0019] More specifically, examples of water reducing agents include lignin sulfonates, oxycarboxylates, naphthalene sulfonates, melamine sulfonates, polystyrene sulfonates, polycarboxylates, and the like.
[0020] As the polycarboxylate-based water reducer, a polymer or copolymer containing a structural unit consisting of a polymer of an α-β unsaturated monocarboxylic acid or a structural unit consisting of a polymer of an α-β unsaturated dicarboxylic acid is preferable, and these may be water-soluble salts.
[0021] More specifically, examples of polycarboxylate-based water reducers include water-soluble salts of copolymers of chain olefins having 5 to 6 carbon atoms and ethylenically unsaturated carboxylic anhydrides, water-soluble salts of copolymers of polyalkylene glycol mono(meth)acrylates and (meth)acrylic acid, water-soluble salts of copolymers of (meth)acrylic acid amides having a sulfonic group at the end, acrylic acid esters and (meth)acrylic acid, water-soluble salts of copolymers of monomers having a sulfonic group, (meth)acrylic acid and other monomers, water-soluble salts of copolymers of monomers having aromatic rings substituted with sulfonic groups and maleic acid, water-soluble salts of copolymers of monomers having a sulfonic group at the end, polyalkylene glycol mono(meth)acrylates, polyalkylene glycol mono(meth)acrylate ethers and (meth)acrylic acid, and water-soluble salts of copolymers of monomers having a polyoxyethylene chain and (meth)acrylic acid. Two or more of these may be used.
[0022] In the above, the polyoxyethylene chain can be represented as (-(OC2H4)nH), where n is the repeating number of polyoxyethylene unit structures, and is preferably in the range of 50 to 200, more preferably 80 to 190, and further preferably 120 to 180.
[0023] Commercially available polycarboxylate-based water-reducing agents include, for example, Melflux (registered trademark; the same applies below) AP 101F, Melflux 2641F, Melflux 2651F, Melflux 5581F, Melflux 4930F, Melflux 6681F, Melflux BF 11F, and Melflux BF 11F(FM) (all manufactured by SKW East Asia Co., Ltd.).
[0024] Commercially available melamine sulfonate-based water-reducing agents include, for example, MELMENT F10M and MELMENT F4000 (both manufactured by SKW East Asia).
[0025] An example of a commercially available naphthalenesulfonate-based water-reducing agent is POWERCON-100 (manufactured by SKW East Asia).
[0026] Commercially available lignin sulfonate-based water-reducing agents include, for example, SODIUM LIGNOSULFNATE ARBO N18 and NORLIG SA (both manufactured by SKW East Asia).
[0027] The amount of the water-reducing agent in the dental glass ionomer cement liquid is preferably 0.01 to 10% by mass. If the amount of the water-reducing agent is 0.01% by mass or more, the cement hardening is prevented from becoming too rapid, and the operation time is extended. If the amount of the water-reducing agent is 10% by mass or less, operability in clinical use is easily ensured. The amount of the water-reducing agent is more preferably 0.1 to 5% by mass, and even more preferably 0.5 to 3.5% by mass.
[0028] The dental glass ionomer cement liquid of the present embodiment may further contain a pH buffer component. By containing the pH buffer component, the dental glass ionomer cement liquid is easily maintained at a low pH (acidic condition), and the hardening reaction is easily allowed to proceed smoothly.
[0029] Examples of pH buffer components include tartaric acid, citric acid, malic acid, ethylenediaminetetraacetic acid, lactic acid, butyric acid, barbituric acid, phosphoric acid, acetic acid, and oxalic acid, as well as water-soluble salts thereof (e.g., sodium salts, potassium salts, etc.), etc. Two or more of these may be used in combination.
[0030] When a pH buffer component is contained, the amount of the pH buffer component in the dental glass ionomer cement liquid is preferably 0.1 to 10% by mass. If the amount of the pH buffer component is 0.1% by mass or more, it is advantageous in that it is easy to ensure a sufficient operating time for clinical use. If the amount of the pH buffer component is 15% by mass or less, it is advantageous in that it hardens sharply. The amount of the pH buffer component is more preferably 1 to 10% by mass.
[0031] The dental glass ionomer cement liquid of the present embodiment can further contain a filler such as silica, (meth)acrylate, a thickener, etc. This makes it possible to make the liquid into a paste, and improves operability.
[0032] In the present specification and claims, the term "(meth)acrylate" refers to various monomers, oligomers, or prepolymers of acrylate or methacrylate, and has one or more (meth)acryloyloxy groups. The term "(meth)acryloyloxy group" refers to a methacryloyloxy group and / or an acryloyloxy group. <Powder ingredients> The powder component is mixed with the dental glass ionomer cement liquid according to this embodiment to provide a hardened dental glass ionomer cement.
[0033] The powder component includes an aluminosilicate glass powder.
[0034] The aluminosilicate glass powder contains aluminum and silicon as components of glass. Therefore, when the dental glass ionomer cement liquid and the powder component are mixed, an acid-base reaction occurs between the aluminosilicate glass powder and the polycarboxylic acid polymer. This acid-base reaction causes ionic cross-linking between the aluminum ions eluted from the aluminosilicate glass powder and the conjugate base of the polycarboxylic acid polymer, resulting in hardening.
[0035] The aluminosilicate glass powder is preferably fluoroaluminosilicate glass, which further contains fluorine as a component of glass, because the inclusion of fluorine improves the caries prevention effect of the dental glass ionomer cement.
[0036] The aluminosilicate glass powder may further contain calcium, phosphorus, strontium, lanthanum, sodium, potassium, nitrogen, magnesium barium, phosphorus, boron, zirconium, tantalum, and the like as glass-constituting components.
[0037] The particle size of the aluminosilicate glass powder is preferably 0.02 to 20 μm in average particle size. If the average particle size exceeds 20 μm, the texture tends to be poor when used as a filling cement, and the abrasion resistance tends to decrease. On the other hand, fine powder with an average particle size of less than 0.02 μm tends to be extremely difficult to mix and to have poor operability. The average particle size is the average value of the major axis and the minor axis (major axis average diameter).
[0038] The refractive index nd of the aluminosilicate glass powder is preferably in the range of 1.42 to 1.47. If the refractive index nd is within this range, the difference with the refractive index nd (about 1.42) of the matrix component of a practically useful dental glass ionomer cement becomes small, and the transparency of the obtained dental glass ionomer cement hardened body becomes high.
[0039] The powder component may further contain a polycarboxylic acid powder, similar to the dental glass ionomer cement liquid. By containing the polycarboxylic acid powder in the powder component, the handling property is improved.
[0040] When a polycarboxylic acid powder is contained in the powder component, the content of the polycarboxylic acid powder is preferably 0.1 to 10% by mass.
[0041] The powder component of this embodiment may further be mixed with water, (meth)acrylate, etc. This makes it possible to make the composition paste-like, improving the ease of use.
[0042] When at least one of the dental glass ionomer cement liquid and the powder component of this embodiment contains (meth)acrylate, a polymerization initiator or a photopolymerization initiator may be further added to at least one of the dental glass ionomer cement liquid and the powder component, which can provide a resin-reinforced glass ionomer cement capable of polymerizing (meth)acrylate by light irradiation or the like, and can provide a hardened cement body with higher physical strength.
[0043] At least one of the dental glass ionomer cement liquid and the powder component of this embodiment may further contain a contrast agent, an antibacterial agent, a fluorescent agent, a fragrance, a pigment, etc., as necessary.
[0044] <Preparation of Dental Glass Ionomer Cement Mixture> When preparing a kneaded product of dental glass ionomer cement, the mass ratio of the powder component to the dental glass ionomer cement liquid (powder-liquid ratio) is preferably 1 to 5. When the powder-liquid ratio is 1 or more, the physical strength of the hardened dental cement is improved. When the powder-liquid ratio is 5 or less, the handling property of the dental cement is improved. The powder-liquid ratio is more preferably 3 to 4.5, and even more preferably 3.2 to 4.
[0045] Dental glass ionomer cement is used by mixing and kneading a powder component and a liquid component to form a mixture, which is applied to the treatment site and then hardened. Before the mixture hardens, it is necessary to move the mixture to the treatment site with a spatula or the like and further adjust the shape.
[0046] In the present invention, the time from the start of kneading until the shape of the kneaded product can no longer be adjusted is defined as the "operation margin time".
[0047] The operating margin time appropriate for clinical use is, for example, from 75 seconds to 600 seconds (10 minutes), more preferably from 90 seconds to 360 seconds (6 minutes).
[0048] The present invention will be described more specifically below with reference to examples and comparative examples, but the present invention is not limited to these examples. EXAMPLES
[0049] <Preparation of aluminosilicate glass powder> 27.5g of silica, 12.7g of alumina, 16.7g of aluminum fluoride, 18.6g of strontium fluoride, 8.8g of aluminum phosphate, 4.2g of sodium fluoride, 5.6g of potassium fluoride, and 5.9g of lanthanum fluoride were thoroughly mixed in a mortar. The mixture obtained was placed in a porcelain crucible and placed in an electric furnace. The electric furnace was heated to 1300°C to melt and homogenize the mixture thoroughly, and then poured into water to obtain aluminosilicate glass lump. The obtained glass lump was pulverized in a ball mill for 20 hours, and then passed through a 120 mesh sieve to obtain aluminosilicate glass powder. <Preparation of powder components> 100 parts by mass of the aluminosilicate glass powder was mixed with 100 parts by mass of a 1% aqueous aluminum phosphate solution to prepare a slurry, which was then dried at 120° C. Polyacrylic acid powder (average molecular weight: 30,000) was mixed with the resulting powder to give a concentration of 3% by mass, to obtain a powder component. <Preparation of dental glass ionomer cement liquid> The components were mixed according to the ratio shown in Table 1 to prepare dental glass ionomer cement liquids of Examples 1 to 13 and Comparative Examples 1 and 2. The unit of the blend amount is mass %.
[0050] The details of the components in Table 1 are as follows: Polyacrylic acid powder: Polyacrylic acid powder with an average molecular weight of 25,000 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Melflux 5581F: Water-soluble salt of copolymer of methacrylic acid and acrylic acid with polyoxyethylene chains manufactured by SKW East Asia Melflux 4930F: Water-soluble salt of copolymer of methacrylic acid and acrylic acid with polyoxyethylene chains manufactured by SKW East Asia Melment F4000: A water-soluble salt of a copolymer of methacrylic acid and acrylic acid with polyoxyethylene chains manufactured by SKW East Asia. <Operation margin time> In a thermostatic room adjusted to 23°C and 50% RH, the dental glass ionomer cement liquids and powder components of Examples 1 to 13 and Comparative Examples 1 and 2 were mixed with a spatula in the powder-liquid ratios shown in Table 1, and kneaded for 30 seconds.
[0051] The kneaded material was collected into a lump, and 75 seconds after the start of kneading, a spatula was attached to it and pulled up, and the degree of adhesion was confirmed. Thereafter, the degree of adhesion to the spatula was checked every 7.5 seconds, and the time from the start of kneading when the kneaded material no longer adhered to the spatula or when it adhered but the shape of the kneaded material could not be adjusted was defined as the operation allowance time.
[0052] The criteria for determining the operation margin time are as follows:
[0053] Excellent: When the operating margin is between 90 and 360 seconds (6 minutes). Good: When the operating margin is between 75 and 90 seconds, or between 360 and 600 seconds (10 minutes) Not allowed: When the operating margin is less than 75 seconds or exceeds 600 seconds <Three-point bending strength test> The dental glass ionomer cement liquids and powder components of Examples 1 to 13 and Comparative Examples 1 and 2 were mixed and kneaded in the powder-liquid ratios shown in Table 1. The kneaded product was placed in a stainless steel mold with a cavity of 2 mm x 2 mm x 25 mm, pressed with a glass plate via cellophane, and removed after 1 hour to obtain a prismatic hardened product. The obtained hardened product was immersed in distilled water at 37°C for 24 hours, and then polished with #320 waterproof abrasive paper to obtain a test specimen.
[0054] The obtained test specimen was subjected to a three-point bending strength test at a crosshead speed of 1 mm / min. using a universal testing machine (product name: Autograph, manufactured by Shimadzu Corporation).
[0055] The criteria for the three-point bending strength are as follows.
[0056] Excellent: Three-point bending strength is 40 MPa or more Good: Three-point bending strength is 35MPa or more and less than 40MPa Not acceptable: If the three-point bending strength is less than 35MPa Table 1 shows the evaluation results of the operation margin time and three-point bending strength test.
[0057] [Table 1] As can be seen from Table 1, when the dental glass ionomer cement liquids of Examples 1 to 13 were used, the evaluation results for both the operating time and the three-point bending strength were excellent or good. This result shows that a hardened cement body with high physical strength can be obtained while ensuring an appropriate operating time for clinical use.
[0058] On the other hand, when the dental glass ionomer cement liquid of the comparative example was used, the three-point bending strength was low when the powder-liquid ratio was 3.4 (Comparative Example 1).When the powder-liquid ratio was 3.8, the hardening was too fast and mixing was not possible, and the working time and three-point bending strength could not be measured (Comparative Example 2).
[0059] While the present invention has been described above based on the embodiment, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the claims.
[0060] This application claims priority from basic application No. 2019-013735, filed on January 30, 2019, with the Japan Patent Office, the entire contents of which are incorporated herein by reference.
Claims
1. The composition contains a polycarboxylic acid polymer, water, a water reducing agent, and a pH buffer component, The polycarboxylic acid polymer is a polymer of an α-β unsaturated monocarboxylic acid or an α-β unsaturated dicarboxylic acid, The water reducing agent is a water-soluble salt of a copolymer of methacrylic acid and acrylic acid having a polyoxyethylene chain, The dental glass ionomer cement liquid, wherein the pH buffer component comprises one or more of tartaric acid, citric acid, malic acid, ethylenediaminetetraacetic acid, lactic acid, butyric acid, barbituric acid, phosphoric acid, acetic acid, and oxalic acid, and water-soluble salts thereof.
2. The composition contains a polycarboxylic acid polymer, water, a water reducing agent, a pH buffer component, and an aluminosilicate glass, The polycarboxylic acid polymer is a polymer of an α-β unsaturated monocarboxylic acid or an α-β unsaturated dicarboxylic acid, The water reducing agent is a water-soluble salt of a copolymer of methacrylic acid and acrylic acid having a polyoxyethylene chain, The dental glass ionomer cement, wherein the pH buffering component comprises one or more of tartaric acid, citric acid, malic acid, ethylenediaminetetraacetic acid, lactic acid, butyric acid, barbituric acid, phosphoric acid, acetic acid, and oxalic acid, and water-soluble salts thereof.
Citation Information
Patent Citations
Liquid hardener for dental glass ionomer cement
JP1977101893A
Preparations for producing materials used especially in the dental field to restore mineralized bodies
JP2005538145A
Glass ionomer cement liquid for dentistry
JP2007091689A
Hardened components
JP2011506367A
Dental cement composition
JP2013053075A